Insights into the molecular regulatory network of pathomechanisms in osteochondroma. Issue 10 (18th June 2019) - Yang, Congyi; Zhang, Ruiqian; Lin, Hui; Wang, Hongmei
Abstract: Osteochondroma is a benign autosomal dominant hereditary disease characterized by abnormal proliferation of cartilage in the long bone. It is divided into solitary osteochondroma and hereditary multiple exostoses (HMEs). The exostosin‐1 ( EXT‐1 ) and exostosin‐2 ( EXT‐2 ) gene mutations are well‐defined molecular mechanisms in the pathogenesis of HME. EXT‐1 and EXT‐2 encode glycosyltransferases that are necessary for the synthesis of heparin sulfate. Accumulating evidence suggests that mutations in the EXT family induce changes in isolated hypogonadotropic hypogonadism‐parathyroid hormone‐related protein, bone morphogenetic protein, and fibroblast growth factor signaling pathways. Studies have also found that a large number of microRNAs (miRNAs) are abnormally expressed in osteochondroma tissues, and some of them also participate in several major signaling pathways. The regulation of miRNA expression could be another breakthrough in the treatment of osteochondroma. Although the pathogenesis of osteochondroma is very complicated, significant progress has been made in recent years. It is hoped that the pathogenesis of osteochondroma will be clearly understood and the most effective methods for the prevention and treatment of osteochondroma will be determined. This review provides an update on the recent progress in the interpretation of the underlying molecular mechanisms of osteochondroma. Abstract : The graphs integrate exostosin ( EXT ) gene mutation with Indian Hedgehog (IHh), bone morphogenetic protein (BMP), and fibroblast growth factor (FGF) signaling pathways in osteochondroma. They may provide a new research direction for the treatment of osteochondroma.